Calibration and Testing of Discrete Element Simulation Parameters for Ultrasonic Vibration-Cutter-Soil Interaction Model - Yang Qiao; Shenghai Huang; Chengyi Yang; Songlin Liu; Kailun Wang; Yunpeng Lu; Jiasheng Wang (Agriculture)
This paper established an accurate discrete element for ultrasonic vibration-cutter-soil interaction model to study the interaction mechanism between the soil-engaging component and the soil. In order to reduce the interaction between calibration parameters and improve the calibration accuracy, it is proposed that the soil constitutive, contact parameters, and bonding parameters be calibrated by combining the soil repose angle experiment and the soil resistance experiment of ultrasonic vibration cutting. The study adopts the Hertz-Mindlin (no slip) contact model used in EDEM, to explore soil particle interactions. The central composite design is used to achieve systematic investigation. 3-factor 3-level orthogonal design experiment was employed using the coefficient of restitution, the coefficient of static friction, and the coefficient of rolling friction as key test factors and soil’s repose angle as the response index. Based on the Hertz-Mindlin with bonding contact model, Design-Expert 13.0 software was used to design the Plackett-Burman experiment, the steepest ascent, and the Box-Behnken experiment. With the maximum soil cutting resistance in ultrasonic vibration cutting experiment used as the response value, the adhesion parameters were optimized, and the optimal solution combination was obtained as: Normal Stiffness = 4.635 × 106 N/m, Shear Stiffness = 3.401 × 106 N/m, and Bonded Disk Radius = 2.57 mm. The optimal parameter combinations obtained from the calibration experiments were verified in two ways: ultrasonic vibration cutting and non-ultrasonic vibration cutting. The results showed that the errors between the simulation values and the actual values of the two comparative experiments were less than 5%, and the model calibrated for the three parameters can be used to study the drag reduction mechanism of ultrasonic vibration cutting in soil.